2016
DOI: 10.4238/gmr.15027627
|View full text |Cite
|
Sign up to set email alerts
|

Expression of miR-98 in myocarditis and its influence on transcription of the FAS/FASL gene pair

Abstract: ABSTRACT. Myocarditis is a common cardiovascular disease and frequently occurs in children and teenagers. It is believed to be caused by both endogenous and exogenous factors, among which FAS/FASL gene pair-induced cell apoptosis is a major mechanism of myocardial cell injury. A previous study has detected low expression of microRNA (miR)-98 in myocarditis patients. Therefore, in this study we investigated the functional implications of miR-98 with respect to the disease. We carried out a case-control study in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…In contrast, Zhang et al found that miR-98 was downregulated in patients with myocarditis, whereas the expression of FAS/FASL was increased 1.68-fold. After performing experiments in cell culture, the authors found that miR-98 targets the FAS/FASL gene pair which can induce apoptosis [41].…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, Zhang et al found that miR-98 was downregulated in patients with myocarditis, whereas the expression of FAS/FASL was increased 1.68-fold. After performing experiments in cell culture, the authors found that miR-98 targets the FAS/FASL gene pair which can induce apoptosis [41].…”
Section: Resultsmentioning
confidence: 99%
“…Then the researchers confirmed miR-34a act as a pro-apoptotic molecule in VMC via targeting the SIRT1-p53 signaling pathway (Jiang et al, 2019 ). In contrast, miR-222, miR-98, and miR-21 may act as anti-apoptotic factors in VMC (He et al, 2013 ; Zhang B. Y. et al, 2016 ; Zhang X. et al, 2019 ). Zhang et al found that the expression of adenosine deaminase, RNA-specific (ADAR1) and miR-222 was increased in CVB3 induced VMC model, and the study in vitro showed that ADAR1 combined Dicer increased cell viability by inducing miR-222 synthesis which decreased the confirmed target phosphatase and tensin homolog (PTEN) expression (Zhang X. et al, 2019 ).…”
Section: The Role Of Mirnas In Cvb3-induced Vmcmentioning
confidence: 99%
“…Hence, ADAR1-Dicer Complex may inhibit cell apoptosis by miR-222 in CVB3 induced VMC. Additionally, MiR-98 decreased cell apoptosis by targeting the FAS/FASL gene (Zhang B. Y. et al, 2016 ), and miR-21 reduced cell apoptosis by targeting programmed cell death 4 (PDCD4) (He et al, 2013 ), a well-known apoptosis gene (Gaur et al, 2011 ; Stagakis et al, 2011 ; Junker et al, 2015 ). Furthermore, another study confirmed that miR-21 reduced cell apoptosis by targeting mitogen-activated protein kinase kinase 3 (MAP2K3) (He et al, 2019 ).…”
Section: The Role Of Mirnas In Cvb3-induced Vmcmentioning
confidence: 99%
“…miRNAs have emerged as key regulators of the immune system, which protect myocarditis against various stimulations by inhibiting apoptosis or targeting nuclear factor kappa-B. [26][27][28] miR-223 was initially described as a modulator of hematopoietic lineage differentiation. 29) Many studies have illustrated that miR-223 can be used as a new potential target for the diagnosis and treatment of inflammatory diseases, such as atopic dermatitis, 30) immune-mediated neuroinflammatory diseases, 31) and acute lung injury.…”
Section: Discussionmentioning
confidence: 99%